Nanophotonics: Hybrid Color Filters for Multispectral Imaging (Adv. Theory Simul. 11/2020). Issue 11 (5th November 2020) - He, Xin; Liu, Yajing; Beckett, Paul; Uddin, Md Hemayet; Nirmalathas, Ampalavanapillai; Unnithan, Ranjith Rajasekharan
Abstract : Multispectral cameras record additional information that a human eye or a normal camera cannot capture. In article number 2000137, Ranjith Unnithan and co‐workers report a hybrid optical filter technology that combines a single plasmonic layer and dielectric layers for multispectral imaging.